Do Not Trust the Pedigree: Reduced and Sex‐Dependent Penetrance at a Novel Mutation Hotspot in ATL1 Blurs Autosomal Dominant Inheritance of Spastic Paraplegia. Issue 6 (5th April 2013) - Varga, Rita‐Eva; Schüle, Rebecca; Fadel, Hicham; Valenzuela, Irene; Speziani, Fiorella; Gonzalez, Michael; Rudenskaia, Galina; Nürnberg, Gudrun; Thiele, Holger; Altmüller, Janine; Alvarez, Victoria; Gamez, Josep; et al.
<x xml:space="preserve">Abstract</x> Inheritance patterns usually guide gene selection in mutational screening strategies. By whole exome sequencing of index cases with apparently novel forms of spastic paraplegia, we identify a mutational hotspot in the known dominant gene ATL1 and show that corresponding alterations are associated with a highly reduced and partially sex‐dependent risk of developing the disease. Our findings suggest that misleading family history may contribute to missing heritability in genetically heterogeneous disorders. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>